SEMIOTIKA DAN RELEVANSINYA DENGAN KAJIAN AL-QUR’AN - Abdul Wadud Kasyful Humam (AL ITQAN: Jurnal Studi Al-Qur'an, 2018)
Considering that the Qur'an consists of a series of Arabic letters arranged in strings of words and sentences, is a medium where signs are messy, so one approach that seems interesting and relevant is the semiotic approach which examines how sign works and its function in the text of the Qur'an. Semiotics  is a discipline that examines signs found in society. Meanwhile, the Al-Qur'an using language as a medium is fertile ground for semiotic studies. In the Qur'an, there are signs that their meanings can be studied by using semiotics. The Qur'an has basic units called verses (signs). Signs in the Qur'an are not only small parts of the elements, such as sentences, words or letters, but the totality of the structures that connect each element is included in the category of signs of the Qur'an. This shows that the entire form of the Qur'an is a series of signs that have meaning.